Handicrafts of Meghalaya: An Analysis of the Marketing Practices - Gupta, Madhuchhanda Das; Sen, Surajit (Indian Journal of Marketing, 2013)
Meghalaya, home to three major tribal groups - the Khasis, the Jaintias and the Garos, is known for its handicrafts. The tribes of Meghalaya are known for weaving artistically designed products that not only have local demand, but also attract tourists. The present study aims at understanding the nature of the handicraft market of the state, and the marketing practices and strategies adopted to position the products. A survey, using a structured schedule, was conducted to ascertain the position of handicrafts marketing in Meghalaya. The survey revealed that cane and bamboo products have the highest demand followed by wooden products. The survey also showed that the market for handicrafts has not yet been optimally tapped. Unorganized structure of the market, unavailability of adequate quantity of quality raw materials, lack of credit, ineffective marketing channels, lack of proper pricing policy and advertising tools have impeded the growth of the handicraft sector. Realizing the importance of developing the industry to generate revenue and employment, the Government of Meghalaya has taken initiatives to organize the artisans into societies and clusters. Training facilities, financial and marketing assistance are also provided by the Government to the craftsmen. There are opportunities galore. The present study indicates that development of efficient marketing channels and implementation of effective marketing strategies can carve a niche market for the handicraft products of Meghalaya globally.